Phenotypicand Genotypic Characterization of Clinical Isolates of Intracellular Adherent–Invasive Escherichia coli Among Different Stages, Family History, and Treated Colorectal Cancer Patients in Iran - Kamali Dolatabadi, Razie; Fazeli, Hossein; Emami, Mohammad Hassan; Karbasizade, Vajihe; Maghool, Fatemeh; Fahim, Alireza; Rahimi, Hojatollah (Frontiers in Cellular and Infection Microbiology, 2022)
There is increasing evidence showing that microbial dysbiosis impacts the health and cancer risk of the host. An association between adherent–invasive Escherichia coli (AIEC) and colorectal cancer (CRC) has been revealed. Cyclomodulins (CMs) have been receiving increasing attention for carcinogenic changes. In this study, the incidence and features of intracellular AIEC and cyclomodulin-encoding genes were investigated and the phylogenetic grouping and genetic relatedness were evaluated. E. coli strains were isolated from the colorectal biopsies. Adhesion and invasion assays and intramacrophage cell survival test were performed to separate the AIEC isolates. Virulence genotyping for the genes htrA, dsbA, chuA, and lpfA and the cyclomodulin toxins was also conducted. In addition, phylogenetic grouping of the isolates was determined. Subsequently, repetitive element sequence-based PCR (rep-PCR) fingerprinting was performed. A total of 24 AIEC pathovars were isolated from 150 patients. The prevalence rates of htr, dsbA, and lpfA were 70.83% and that of chuA was 91.66%. The frequencies of the cyclomodulin toxins were as follows: cnf1, 29.2%; cnf2, 25%; colibactin, 29.2%; and cdt, 4.2%; cif was not found. Among the AIEC isolates, 4.2%, 4.2%, 54.2%, 29.2%, and 8.3% with phylotypes A or C, B1, B2, D, and E were identified, respectively. Left-sided colon carcinoma and adenocarcinoma T≥1 stage (CRC2) were colonized by B2 phylogroup AIEC-producing CMs more often than the samples from the other groups. Close genetic relatedness was observed in AIEC isolates with rep-PCR.